Molecular pilot study on peripheral populations of Kenyan greenbul in an afromontane fragmented forest. (19th February 2018) - De Santis, Vanessa; Mwinami, Timothy; Chesire, Dominic; Musina, John; Zaccara, Serena; Kioko, Esther; Owino, Junga J.; Oduma, Jemimah A.; Ayiemba, Washington; Harper, David M.; Crosa, Giuseppe
Abstract: We provide a molecular study on peripheral populations of three closely related species of African forest‐dependent greenbuls: the generalist Eurillas latirostris and the specialists Phyllastrephus cabanisi and Arizelocichla nigriceps . These species co‐occur within their range limits in the Kenyan Afromontane forest, Cherangani Hills. This forest has experienced drastic deforestation, which began about 50 years ago, that is causing habitat fragmentation. The aims of this study, using the analyses of molecular tools, are twofold: (i) to provide evidence that functional traits (i.e., ecological attributes) may shape different genetic structure in peripheral populations and (ii) to identify the possible effects of forest fragmentation. Blood and plucked feathers were sampled from a total of 124 birds analysed using two molecular approaches: (i) sequencing of cytochrome b mtDNA and (ii) genotyping nuclear DNA at eight microsatellite loci. Molecular diversity indices, minimum spanning network and mismatch distribution analysis of mtDNA results indicated that the peripheral populations showed different demographic trends: a highly variable and bimodal pattern in forest specialist P. cabanisi, a less variable and unimodal pattern in forest generalist E. latirostris and in the montane specialist A. nigriceps . Although this is a pilot study on the Cherangani forest fragmentation, the nuclear results may not exclude the hypothesis of reduced connectivity in all forest‐dependent greenbuls.